Kehipnosisan Al-Qur’an (Sebuah Metodologis dalam Mengkaji Daya ‘Ijaz Al-Qur’an) - Inan Tihul (STIT Muslim Asia Afrika, 2021)
The Qur'an constantly challenges all Arab literature experts to try to be matched. But no one is able to answer the challenges of the Qur'an. They are not even able to imitate, because the Qur'an is on top of a peak that is impossible to excel. And the Qur'an is not a human sentence. That paves the way for experts to be able to uncover aspects of balaghah (rhetoric), the Qur'an and its unique language style in formulating sentence arrangements to describe something. The Arabic linguists have shed all their cherished and grateful activities. They try hard to present balaghah al-Qur'an in the form of inspiration that is fun. On the scientific aspect, the scientificity of the Qur'an does not lie in its scope to the ever-new and changing scientific theories as a result of human effort through observation and research, but lies in its spirit of encouraging people to think using their minds. All problems or rules of science that have been established and convincing, is a manifestation of the activities of thinking recommended by the Qur'an. The Qur'an has rebuilt every Muslim's scientific consciousness to think, understand, and use reason. In contrast to the understanding of most people, who say that when in a state of hypnosis or trance one's consciousness is very weak, when in a trance condition the level of consciousness of a person actually increases very high.